Demography of Hyperuricemia and its Association with Metabolic Syndrome (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Hyperuricemia and gout are associated with significant mortality. The mortality may be caused by hyperuricemia itself or its association with metabolic syndrome.Objectives:To find out the association of hyperuricemia and metabolic syndrome.Materials and Methods: This cross-sectional observational study was conducted in CMH Dhaka and KGH, Dhaka from February to July 2019. Both indoor and outdoor patients were enrolled to see the level of uric acid and associated diseases and conditions, especially the metabolic syndromes. Total 800 patients were tested out of which 100 were hyperuricemic (Group A). Group A were compared with 100 age and sex matched control with normal uric acid level (Group B). Chi square test was done to see the level of significance.Results: Total 800 respondents were tested for serum uric acid. Male were 500 (62.50%) and female were 300 (37.50%). Normal serum uric acid was found in 700 (87.5%) and hyperuricemia were found in 100 (12.5%) cases. Majority of respondents were included in age group 41-60 and 61-80 years. Number of hyperuricemias in these two groups were 50 (12.5%) and 30 (20%) and number of gouts were 14 (3.5%) and 12 (8%) respectively. In group A 30 (30%) had gout and 70 (70%) were asymptomatic. Both hyperuricemia and gout were far more in male compared to female, hyperuricemia in 16% vs 6.66% and gout in 4.40% vs 2.66% respectively. Majority of hyperuricemic patients were serving, 30 (30%) and retired group 25 (25%). Number of HTN, DM, abdominal obesity, dyslipidemia and CKD were more in Group A as compared to Group B. In group A there were 35 metabolic syndromes and in group B there were only 15 metabolic syndromes. The difference is statistically significant (p value